1970
DOI: 10.1111/j.1365-2621.1970.tb00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity as Affected by Various Constituents of Tomato Juice

Abstract: SUMMARY— Degradation of proteins of tomato juice with pronase caused a relatively small loss of viscosity. Commercial cellulase freed of pectolytic activity with 8 M urea greatly decreased the viscosity of washed tomato solids. Further degradation with pectinase was ineffective in reducing viscosity. Cellulase extracted from the tomato lowered viscosity of tomato juice. Enzymatic degradation as indicated by chemical analysis did not always result in a loss of viscosity. By extracting the solids with water, vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 7 publications
2
17
0
Order By: Relevance
“…These results are in agreement with previous studies reporting a reduced viscosity of tomato juices on adding cellulases and pectinases . These authors established that polymeric compounds such as pectin and cellulose contribute majorly to the consistency of tomato juices.…”
Section: Resultssupporting
confidence: 93%
“…These results are in agreement with previous studies reporting a reduced viscosity of tomato juices on adding cellulases and pectinases . These authors established that polymeric compounds such as pectin and cellulose contribute majorly to the consistency of tomato juices.…”
Section: Resultssupporting
confidence: 93%
“…Some researchers reported that when using hot-break method, the temperatures are high enough for pectolytic enzyme inactivation, and this leads to a concentrate of greater viscosity (Fito, Clemente, & Sanz, 1983;Goodman et al, 2002). In addition, break temperature influences the viscosity of tomato products by changing pectin retention (Xu, Shoemaker, & Luh, 1986), but the effect was eliminated due to the insignificant contribution of pectins to the viscosity of tomato juice (Foda & McCollum, 1970). Therefore, this study mainly showed that viscosity differences are caused by enzyme activity.…”
Section: Viscositymentioning
confidence: 82%
“…The higher consistency of the low pH sample may be due to two reasons: (a) the increased pectin contents (0.31%) or (b) the presence of increased levels of low methoxyl pectin in this sample. Higher levels of pectic substances have been demonstrated to increase the consistency of tomato juice by a number of workers (McColloch, Keller & Beavans, 1952;Hand et af., 1955;Foda & McCollum, 1970). According to Padiwal, Ranganna & Manjrekar (1979), the gel formation involves the transformation of a sol state of Low Methoxyl Pectin (LMP) to the gel state caused by added calcium.…”
Section: Colour and Consistencymentioning
confidence: 99%